Long-lasting Labour Market Consequences of German Unification - Joachim Möller; Uwe Blien; Phan thi Hong Van; Stephan Brunow (European Regional Science Association (ERSA), 2015)
This article shows how the impulses of the transformation process in eastern Germany have spread through the economy and the labour market. The form of transformation has long-term effects on the form of control over the economy; it is managed largely from western firms. This fact has manifold consequences for the innovation behaviour of plants, among others, which in turn is further related to productivity and thus to the labour market. We argue that this transfers further to persistently lower wages and higher unemployment rates in eastern compared with western Germany.
Keywords: J24; J31; R12; 330; Regional Unemployment; Regional Wage Dynamics; Innovation; Human Capital